Designing a Functional Approach Daily Conversation Module for Beginner EFL Learners - Aris Dwi Intan Aprianti; Iwan Jazadi; Sartika Sartika; Elli Marliana (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2025)
Communicating effectively in daily conversations remains a challenge for many Indonesian EFL learners, particularly beginners, who often struggle with fluency, vocabulary limitations, and a lack of confidence. This study aimed to design, develop, and validate a contextual daily conversation module using the Functional Approach within the ADDIE instructional model. A needs analysis involving students, alumni, and a course coordinator revealed learners’ preference for contextual topics, scaffolded practice, and bilingual support. The design phase translated these findings into structured lesson plans and communicative tasks, while the development phase involved expert validation to refine the module. The novelty of this study lies in its integration of the Functional Approach with bilingual scaffolding, a combination rarely explored in Indonesian tertiary EFL contexts. The resulting module features functional expressions, bilingual glossaries, authentic conversational topics, and reflective activities, all validated as highly appropriate by experts. Beyond its immediate context, the module provides a scalable model for other institutions seeking to enhance students’ communicative competence through context-responsive materials.